2005
DOI: 10.1007/s10350-004-0752-3
|View full text |Cite
|
Sign up to set email alerts
|

Value of Hydrogen Peroxide Enhancement of Three-Dimensional Endoanal Ultrasound in Fistula-in-Ano

Abstract: In recurrent or complex fistula-in-ano, endoanal ultrasound proved more accurate for detecting primary tracks and internal openings than for detecting extensions. Hydrogen peroxide improved conspicuity of some tracks and internal openings and so may be helpful in difficult cases, although no overall diagnostic benefit was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0
8

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 18 publications
6
39
0
8
Order By: Relevance
“…In the present study, the agreement of 3D-EAUS with surgery was excellent: 84% in the detection of primary tracts, 84% in internal openings, and 82% in secondary extensions. These outcomes are consistent with recent data concerning 3D-EAUS [16][17][18] . Most reports using conventional 2D-EAUS have shown superior results with H2O2 enhancement.…”
Section: Kim Y Et Al Endoanal Ultrasound In Anal Fistulasupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, the agreement of 3D-EAUS with surgery was excellent: 84% in the detection of primary tracts, 84% in internal openings, and 82% in secondary extensions. These outcomes are consistent with recent data concerning 3D-EAUS [16][17][18] . Most reports using conventional 2D-EAUS have shown superior results with H2O2 enhancement.…”
Section: Kim Y Et Al Endoanal Ultrasound In Anal Fistulasupporting
confidence: 93%
“…Another point to consider is that although H2O2 enhancement had little influence on diagnostic accuracy improvement, H2O2 enhancement often improved the quality of images in cases where the unenhanced study barely delineated the tract as shown in Figure 1 of this study and in another report [17] . The presence of gas in the internal opening or fistula track made the tract more obvious.…”
Section: Kim Y Et Al Endoanal Ultrasound In Anal Fistulamentioning
confidence: 56%
See 2 more Smart Citations
“…Optimizing the combined ultrasound approaches, we can inject saline with little air or dilute hydrogen peroxide into the fistula track which helps to discover the site of internal opening by detecting gas bubble emerging from its site and to detect multiplicity of internal opening [15] . Adding to the advantages of the technique is the real time imaging of saline mixed with air bubbles or hydrogen peroxide flowing inside the track, which helps to detect obstructed tracks that may contribute to false passage during probing.…”
Section: Discussionmentioning
confidence: 99%